A new species, genus and tribe of cicada (Hemiptera: Cicadoidea: Cicadidae: Tibicininae) from Chile with a list of Chilean cicada fauna - Sanborn, Allen F. (Zootaxa, 2021)
Citroriginini n. tribe. is formed for the Chilean cicada Citroriginis elongata n. gen., n. sp. Males differ from other South American Tibicininae Distant, 1905a because they lack timbal organs. The new species has fore wings that are similar in general appearance to the Nearctic Platypediini Kato, 1932 and genitalia with a superficial resemblance to the Tettigadini Distant, 1905c and the Chilean Chilecicadini Sanborn, 2014 but the new species is divergent from the both tribes in the fore wing venation, fore wing cell shape, general body proportions and male genitalia. A female exuvia is described representing the first description of a Chilean cicada exuvia. A list of Chilean cicada species is also provided with Calliopsida cinnabarina (Berg, 1879) removed from the Chilean cicada fauna.